Managing gastrointestinal involvement in cutaneomucosal venous malformation: safety and efficacy of endoscopic sclerotherapy - Jiaxue Zhu; Wei Liu; Zehua Zhang; Bensong Duan; Xiaohan Yan (Hereditas)
Abstract Blue rubber bleb nevus syndrome (BRBNS) and cutaneomucosal venous malformation (VMCM) both manifest as venous malformations (VMs) characterized by blue, compressible nodules. While BRBNS typically involves visceral organs, particularly the gastrointestinal (GI) tract, VMCM has conventionally been considered to spare internal organs. Our findings, however, reveal that VMCM can indeed extend to the GI system and demonstrate that endoscopic sclerotherapy is safe and effective for its management. This underscores the importance of genetic testing and systemic evaluation in patients with multifocal VMs, suggesting the need for revised diagnostic criteria and a more nuanced approach to classification of these disorders.